Effectiveness of Stress Management and Work Motivation Development Training for Housewives and Workers - Hasyim, Hasyim; Bakri, Muhammad (Celebes Journal of Community Services, 2023)
This study aims to investigate the effectiveness of integrating stress management and work motivation development training for housewives and workers, focusing on how combined interventions impact stress reduction, motivation enhancement, and overall well-being. A systematic literature review (SLR) methodology was employed to analyze and synthesize studies from 2018 onward that explore the intersection of stress management and motivation development for housewives and workers. Relevant studies were selected from academic databases, and findings were assessed to identify trends, gaps, and the effectiveness of integrated interventions. The study found that integrated programs combining stress management techniques with motivational strategies led to significant improvements in stress reduction and motivation. While both housewives and workers showed positive outcomes, workers demonstrated more pronounced improvements in productivity and job satisfaction due to the structured nature of workplace settings. Housewives, however, experienced greater emotional well-being improvements but faced challenges in accessing formal programs due to time constraints and societal norms. The study highlights the potential of integrated interventions in improving personal and professional outcomes for both housewives and workers. It provides practical insights for policymakers and organizations in designing inclusive, flexible programs that address the unique needs of these groups. The findings suggest that combining stress management with motivation can lead to more sustainable behavioral changes, benefiting both well-being and productivity. Future research should expand the scope to include long-term effects and explore cultural differences in program efficacy.